The first example of the stereoselective synthesis and crystal structure of a spirobicycloquinazolinone based on (–)‐fenchone and anthranilamide. Issue 12 (26th November 2019) - Chernyshov, Vladimir V.; Gatilov, Yuri V.; Yarovaya, Olga I.; Koskin, Igor P.; Yarovoy, Spartak S.; Brylev, Konstantin A.; Salakhutdinov, Nariman F.
Abstract : The possibility of a one‐stage solvent‐free stereoselective synthesis of a spirocyclic quinazoline derivative is described for the first time. An X‐ray diffraction study of the crystal structure of the chiral spirocyclic compound obtained was carried out and its porosity was studied. Abstract : The possibility of a single‐stage solvent‐free stereoselective synthesis of a spirocyclic compound from the natural bicyclic monoterpenoid (−)‐fenchone and anthranilamide has been shown for the first time. The molecular and crystal structure of (1 R, 2 S, 4 S )‐1, 3, 3‐trimethyl‐1′ H ‐spiro[bicyclo[2.2.1]heptane‐2, 2′‐quinazolin]‐4′(3′ H )‐one, C17 H22 N2 O, was established by X‐ray diffraction though the chirality was assumed via the known reactant connectivity and 1 H and 13 C NMR spectroscopy. It has shown that in the molecule, for steric reasons, there is an elongation of the Me2 C—C(N)N bond to 1.603 (5) Å. The formation of dimers via N—H…O=C hydrogen bonds with an interaction energy of 93.30 kJ mol −1 and through cavities (33.7% of the unit‐cell volume) was established in the packing of the molecules. There are no π‐stacking interactions in the structure.